Enhancing s-CO2 Brayton Power Cycle Efficiency in Cold Ambient Conditions Through Working Fluid Blends - Paul Tafur-Escanta; Luis Coco-Enríquez; Robert Valencia-Chapi; Javier Muñoz-Antón (Entropy, 2025)
Supercritical carbon dioxide (s-CO2) Brayton cycles have emerged as a promising technology for high-efficiency power generation, owing to their compact architecture and favorable thermophysical properties. However, their performance degrades significantly under cold-climate conditions—such as those encountered in Greenland, Russia, Canada, Scandinavia, and Alaska—due to the proximity to the fluid’s critical point. This study investigates the behavior of the recompression Brayton cycle (RBC) under subzero ambient temperatures through the incorporation of low-critical-temperature additives to create CO2-based binary mixtures. The working fluids examined include methane (CH4), tetrafluoromethane (CF4), nitrogen trifluoride (NF3), and krypton (Kr). Simulation results show that CH4- and CF4-rich mixtures can achieve thermal efficiency improvements of up to 10 percentage points over pure CO2. NF3-containing blends yield solid performance in moderately cold environments, while Kr-based mixtures provide modest but consistent efficiency gains. At low compressor inlet temperatures, the high-temperature recuperator (HTR) becomes the dominant performance-limiting component. Optimal distribution of recuperator conductance (UA) favors increased HTR sizing when mixtures are employed, ensuring effective heat recovery across larger temperature differentials. The study concludes with a comparative exergy analysis between pure CO2 and mixture-based cycles in RBC architecture. The findings highlight the potential of custom-tailored working fluids to enhance thermodynamic performance and operational stability of s-CO2 power systems under cold-climate conditions.